2000
DOI: 10.1007/s004290000137
|View full text |Cite
|
Sign up to set email alerts
|

The subrhinal paleocortex in the hedgehog tenrec: a multiarchitectonic characterization and an analysis of its connections with the olfactory bulb

Abstract: In the Madagascan hedgehog tenrec, Echinops telfairi, the entire paleocortical region (PCx) subjacent to the rhinal indentation is composed of three layers and occupies up to two thirds of the lateral hemisphere. A clear differentiation of PCx into its presumed constituents, the piriform cortex and the entorhinal cortex, as seen in other mammals, has not been obtained so far. To gain insight into location and intrinsic organization of these areas in a basal placental mammal we investigated the tenrec's PCx usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…In both monotremes the OT is small and poorly developed; in the platypus this means small in absolute terms (less than 1.5 mm eutheria occupying a similar insectivorous niche [Künzle and Radtke-Schuller, 2000]. As previously reported [Ashwell, 2006], the olfactory bulb of the echidna is comparable in volume to prosimians of similar body weight and comparable in absolute terms to the volume of the olfactory bulbs of the largest eutherian insectivores.…”
Section: Evolutionary and Functional Considerationssupporting
confidence: 59%
See 1 more Smart Citation
“…In both monotremes the OT is small and poorly developed; in the platypus this means small in absolute terms (less than 1.5 mm eutheria occupying a similar insectivorous niche [Künzle and Radtke-Schuller, 2000]. As previously reported [Ashwell, 2006], the olfactory bulb of the echidna is comparable in volume to prosimians of similar body weight and comparable in absolute terms to the volume of the olfactory bulbs of the largest eutherian insectivores.…”
Section: Evolutionary and Functional Considerationssupporting
confidence: 59%
“…In previous studies on the cerebral cortex and claustrum of the echidna [Abbie, 1940;Hassiotis et al, 2004;Ashwell et al, 2004], the olfactory tubercle of the echidna has been noted in passing, but those studies did not fully describe this region. In therian mammals, particularly those occupying a similar niche to the echidna, the olfactory tubercle is an extensive strongly laminated structure [Oswaldo-Cruz and Rocha-Miranda, 1968;Künzle and Radtke-Schuller, 2000], where olfactory information gains access to the ventral striatum [Shipley et al, 1995]. However, initial inspection of the echidna olfactory tubercle revealed that this region was remarkably underdeveloped compared to the extensive echidna piriform lobe [Hassiotis et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The material and methods used are largely the same as described in the previous papers (Radtke-Schuller and Künzle 2000; Künzle and Radtke-Schuller 2000). In short, the lesser hedgehog tenrecs (Echinops telfairi, Et), obtained from our breeding colony (Künzle 1998) were anesthetized with tribromoethanol (1.0 ml/ 100 gm, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…A broadly similar laminar distribution of type I NADPH-d-reactive neurons has been noted for the Madagascan hedgehog tenrec [ Echinops telfairi , Künzle and Radtke-Schuller, 2000], some rodents [Davis, 1991;Paxinos et al, 1999] and some carnivores [Mizukawa et al, 1989].…”
Section: Cyto-and Chemoarchitecture Of the Monotreme Piriform Cortex:mentioning
confidence: 73%
“…Immunoreactivity for the calcium-binding proteins reveals distinct subclasses of neurons in therian AO and Pir [Celio, 1990;Résibois and Rogers, 1992;Frassoni et al, 1998;García-Ojeda et al, 1998;Paxinos et al, 1999;Künzle and Radtke-Schuller, 2000;Barbado et al, 2002] and was found to distinguish subregions within the echidna Pir. Immunoreactivity for TH and enzyme reactivity for NADPH diaphorase also label discrete subpopulations of neurons in the anterior olfactory nucleus and piriform cortex [Mizukawa et al, 1989;Paxinos et al, 1999;Künzle and Radtke-Schuller, 2000]. The aim of the present study was to determine what similarities and differences in cyto-and chemoarchitectural organization of these two cortical olfactory areas exist both between the echidna and the platypus and between both monotremes and therian mammals, and to try to interpret these fi ndings in evolutionary and functional contexts.…”
Section: Introductionmentioning
confidence: 99%